Plasmonic antennas based on rectangular graphene nanoribbons with controlled polarization of terahertz and infrared radiation - Galina S. Makeeva (Физика волновых процессов и радиотехнические системы, 2024)
Background. To develop new terahertz wireless communication systems with high throughput and transmission speeds, such as 6G and above, effective control of the polarization direction of emitted terahertz waves is necessary, but most methods are technologically complex and expensive. The implementation of terahertz antennas and devices based on 2D materials such as graphene solves the problem associated with developing effective control. Aim. Study of the possibility of controlling the polarization of terahertz and IR radiation of plasmonic antennas based on rectangular graphene nanoribbons by changing the chemical potential (application of an external electric field). Methods. This important scientific problem related to the design of terahertz antennas can largely be solved by simulation using the electrodynamic simulation program CST MWS 2023. Results. Plasmon terahertz antennas based on rectangular graphene nanoribbons were chosen as the object of analysis and the possibility of emitting waves of two orthogonal polarizations was shown. Methods have been identified for controlling the polarization of terahertz and IR radiation from such antennas, based on the selection of operating frequencies corresponding to the resonances of the modes of surface plasmon-polaritons, and the application of metallization to the dielectric substrate. Conclusion. The ability to control the polarization of terahertz and IR radiation makes it possible to create both new elements of plasmonic antenna arrays and new communication technologies, including future 6G networks.